Monitoring the price and affordability of foods and diets globally. (17th September 2013) - Lee, A.; Mhurchu, C. N.; Sacks, G.; Swinburn, B.; Snowdon, W.; Vandevijvere, S.; Hawkes, C.; L'Abbé, M.; Rayner, M.; Sanders, D.; Barquera, S.; Friel, S.; et al.
Summary: Food prices and food affordability are important determinants of food choices, obesity and non‐communicable diseases. As governments around the world consider policies to promote the consumption of healthier foods, data on the relative price and affordability of foods, with a particular focus on the difference between 'less healthy' and 'healthy' foods and diets, are urgently needed. This paper briefly reviews past and current approaches to monitoring food prices, and identifies key issues affecting the development of practical tools and methods for food price data collection, analysis and reporting. A step‐wise monitoring framework, including measurement indicators, is proposed. 'Minimal' data collection will assess the differential price of 'healthy' and 'less healthy' foods; 'expanded' monitoring will assess the differential price of 'healthy' and 'less healthy' diets; and the 'optimal' approach will also monitor food affordability, by taking into account household income. The monitoring of the price and affordability of 'healthy' and 'less healthy' foods and diets globally will provide robust data and benchmarks to inform economic and fiscal policy responses. Given the range of methodological, cultural and logistical challenges in this area, it is imperative that all aspects of the proposed monitoring framework are tested rigorously before implementation.